Adsorption of Pb(II) and Cd(II) by magnetic activated carbon and its mechanism - Zhang, Zhen; Wang, Tao; Zhang, Huixue; Liu, Yonghong; Xing, Baoshan (The Science of the total environment, 2021)
Magnetized activated carbons (MAC) were prepared by activating rape straw powder, and pyrolyzing at different temperatures, then magnetizing activated carbon by hydrothermal method. MAC-300 had the largest adsorption capacity of Pb(II) (253.2 mg/g) and Cd(II) (73.3 mg/g). The adsorption isotherms and kinetics could conform to the Freundlich model and pseudo-second-order kinetic model, respectively, indicating that the adsorptive behavior of the adsorbent mainly depends on the non-uniform active points on the surface of the material. Meanwhile, the thermodynamic parameters showed that the adsorption of Pb(II) and Cd(II) by MAC-300 was a spontaneous and endothermic reaction. The adsorption capacity of MAC-300 could be improved by properly increasing the pH of the original solution. There was competitive adsorption when high-valent ions were present in solution. In combination with various characterizations and comparison tests of samples after adsorption, the adsorption mechanisms include surface electrostatic attraction, surface complexation, and co-precipitation. The results indicated that the MAC material was a potential material to remove heavy metal ions from the aqueous solution. [Display omitted] •Activation carbon embedded with MnFe2O4 magnetic particles (MAC-T) was fabricated.•MAC-T had excellent ferromagnetic properties, stability, and reusability.•MAC-T showed high adsorption ability for Pb(II) and Cd(II).•The mechanisms were electrostatic attraction, complexation, and co-precipitation.